Provincialism or a world-class system? : Is German vocational education and training fit for internationalisation? - Kremer, Manfred [Verfasser] (My University, 2007)
In the current debate on a possible reform of the education systems, the President of the Federal Institute for Vocational Education and Training, Manfred Kremer, calls for a greater flexibility of pathways, especially easier transistions between vocational education and higher education. The European Qualfications Framework (EQF) and the European Credit System in Vocational Education and Training (ECVET) are viewed as an opportunity to redress the undervaluing of in-company vocational training in Europe. (BIBB)
Keywords: S 2.3 Berufsbildungspolitik; I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; G 2.5.3 Anschlussfähigkeit von Bildungsgängen; Berufsbildung; Internationalisierung; Interkulturelle Kompetenz; Berufliche Qualifikation; Anerkennung; Durchlässigkeit im Bildungssystem